Evolvement of syncretic music: the aesthetic values of Malaysian popular and traditional music - Ismail, Md Jais; Loo, Fung Chiat (Babes-bolyai University, 2023)
Malaysian music was influenced by British, Portuguese, Indian, and Chinese cultures, which created syncretic music. Aesthetics values strengthen the existence of syncretic music by molding taste and interest among the listeners. It somehow creates various feelings whether to appreciate, accept, or against the music, further developing musical preferences among individuals. Exploring aesthetic values in popular and traditional music is crucial as many cultures have influenced Malaysia due to colonization, trading, wedding, and migration. This paper reviews on Malaysian syncretic music, the aesthetic values in Malaysian popular and traditional music, and the influence factors of Malaysian music. It is found that there was a confluence of various intercultural musical elements in the early era, while assimilation has taken place due to traditional Malay rhythmic patterns and traditional folk themes. This led to the Malaysian conception of music and musical composition, creating the idea that Malaysian music has drastically expanded its artistic resources since the pre-colonial era. We also found communities living in the pre-modern or modern era have different unique taste in the aesthetic characteristics. Despite this, most remote communities are compelled to participate in postmodernity in some way due to the globalization of media, capital, and mobile networks. These combinations result in many theories, concepts, and discourses that enrich aesthetic values in Malaysian syncretic music.